Criterion-Referenced Values of Grip Strength and Usual Gait Speed Using Instrumental Activities of Daily Living Disability as the Criterion. Issue 1 (January 2018) - Lee, Meng-Chih; Hsu, Chih-Cheng; Tsai, Yi-Fen; Chen, Ching-Yu; Lin, Cheng-Chieh; Wang, Ching-Yi
Abstract : Background and Purpose: Current evidence suggests that grip strength and usual gait speed (UGS) are important predictors of instrumental activities of daily living (IADL) disability. Knowing the optimum cut points of these tests for discriminating people with and without IADL disability could help clinicians or researchers to better interpret the test results and make medical decisions. The purpose of this study was to determine the cutoff values of grip strength and UGS for best discriminating community-dwelling older adults with and without IADL disability, separately for men and women, and to investigate their association with IADL disability. Methods: We conducted secondary data analysis on a national dataset collected in the Sarcopenia and Translational Aging Research in Taiwan (START). The data used in this study consisted of health data of 2420 community-dwelling older adults 65 years and older with no history of stroke and with complete data. IADL disability was defined as at least 1 IADL item scored as "need help" or "unable to perform." Receiver operating characteristics analysis was used to estimate the optimum grip strength and UGS cut points for best discriminating older adults with/without IADL disability. The association between each physical performance (grip strength and UGS) and IADL disability was assessed with odds ratios (ORs). Results and Discussion: With IADL disability as the criterion, the optimal cutoff values of grip strength were 28.7 kg for men and 16.0 kg for women, and those for UGS were 0.76 m/s for men and 0.66 m/s for women. The grip strength test showed satisfactory discriminant validity (area under the curve > 0.7) in men and a strong association with IADL disability (OR > 4). Our cut points using IADL disability as the criterion were close to those indicating frailty or sarcopenia. Conclusions: Our reported cutoffs can serve as criterion-referenced values, along with those previously determined using different indicators, and provide important landmarks on the performance continua of older adults' grip strength and UGS. These landmarks could be useful in interpreting test results, monitoring changes in performance, and identifying individuals requiring timely intervention. For identifying older adults at risk of IADL disability, grip strength is superior to UGS.